2020
DOI: 10.1105/tpc.20.00192
|View full text |Cite
|
Sign up to set email alerts
|

COLD-REGULATED GENE27 Integrates Signals from Light and the Circadian Clock to Promote Hypocotyl Growth in Arabidopsis

Abstract: Light and the circadian clock are two essential external and internal cues affecting seedling development. COLD-REGULATED GENE27 (COR27), which is regulated by cold temperatures and light signals, functions as a key regulator of the circadian clock. Here, we report that COR27 acts as a negative regulator of light signaling. COR27 physically interacts with the CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1)-SUPPRESSOR OF PHYTOCHROME A1 (SPA1) E3 ubiquitin ligase complex and undergoes COP1-mediated degradation via the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 71 publications
6
50
0
Order By: Relevance
“…Both studies set out to test whether impairment of COR27 function affected PIF4 mRNA levels. Zhu et al (2020) detected reduced PIF4 mRNA levels in the cor27 mutant in the afternoon, but not at other time-points over the course of a 12 h light/12 h dark diurnal cycle. By contrast, Li et al (2020) observed lower PIF4 expression in the cor27 cor28 mutant at night in seedlings grown in short days (8 h light/ 16 h dark), but did not test other time-points.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…Both studies set out to test whether impairment of COR27 function affected PIF4 mRNA levels. Zhu et al (2020) detected reduced PIF4 mRNA levels in the cor27 mutant in the afternoon, but not at other time-points over the course of a 12 h light/12 h dark diurnal cycle. By contrast, Li et al (2020) observed lower PIF4 expression in the cor27 cor28 mutant at night in seedlings grown in short days (8 h light/ 16 h dark), but did not test other time-points.…”
mentioning
confidence: 74%
“…The studies by Li et al (2020) and Zhu et al (2020) present strong evidence for a COP1dependent role of COR27 and COR28 in the promotion of hypocotyl growth. How this effect is executed through downstream targets, such as HY5 and potentially other transcription factors, will be the next pieces to place in the puzzle of temperature, light and circadian clock signaling.…”
mentioning
confidence: 84%
See 3 more Smart Citations